Motif Penggunaan Second Account Instagram bagi Pelajar SMK Negeri 1 Gempol - Farah Nabilah; Kukuh Sinduwiatmo (Jurnal Nomosleca, 2023)
Internet information technology spurred the existence of social media platforms that make it easier for users to interact via Instagram with second accounts. The purpose of this research is to find out the motives of students at SMK Negeri 1 Gempol in using second Instagram accounts. Erving Goffman's dramaturgical theory is combined with qualitative descriptive methods in analyzing motives. Ten informants as a source of data resulting from interviews. The results of this study explain the motives of students at SMK Negeri 1 Gempol in using second accounts on Instagram, namely as a place to store their work and hide the user's real identity from other people. Meanwhile, the motive for using the main account owned by Gempol 1 Public Vocational School students is as a place to brand themselves by sharing positive content.Â